Study protocol for a randomised controlled trial evaluating the effect of prenatal omega-3 LCPUFA supplementation to reduce the incidence of preterm birth: the ORIP trial. Issue 9 (24th September 2017) - Zhou, Shao J; Best, Karen; Gibson, Robert; McPhee, Andrew; Yelland, Lisa; Quinlivan, Julie; Makrides, Maria
Abstract : Introduction: Preterm birth accounts for more than 85% of all perinatal complications and deaths. Seventy-five per cent of early preterm births (EPTBs) occur spontaneously and without identifiable risk factors. The need for a broadly applicable, effective strategy for primary prevention is paramount. Secondary outcomes from the docosahexaenoic acid (DHA) to Optimise Mother Infant Outcome trial showed that maternal supplementation until delivery with omega-3 (ω-3) long chain polyunsaturated fatty acid (LCPUFA), predominantly as DHA, resulted in a 50% reduction in the incidence of EPTB and an increase in the incidence of post-term induction or post-term prelabour caesarean section due to extended gestation. We aim to determine the effectiveness of supplementing the maternal diet with ω-3 LCPUFA until 34 weeks' gestation on the incidence of EPTB. Methods and analysis: This is a multicentre, parallel group, randomised, blinded and controlled trial. Women less than 20 weeks' gestation with a singleton or multiple pregnancy and able to give informed consent are eligible to participate. Women will be randomised to receive high DHA fish oil capsules or control capsules without DHA. Capsules will be taken from enrolment until 34 weeks' gestation. The primary outcome is the incidence of EPTB, defined as delivery before 34 completed weeks' gestation. Key secondary outcomes include length of gestation, incidence of post-term induction or prelabour caesarean section and spontaneous EPTB. The target sample size is 5540 women (2770 per group), which will provide 85% power to detect an absolute reduction in the incidence of preterm birth of 1.16% (from 2.45% to 1.29%) between the DHA and control group (two sided α=0.05). The primary analysis will be based on the intention-to-treat principle. Trial registration number: Australia and New Zealand Clinical Trial Registry Number: 2613001142729; Pre-results.